Pengaruh Komitmen Karyawan Dan Pelatihan Terhadap Produktivitas Kerja Karyawan Departemen Pelayanan PT. PLN (Persero) Cabang Selatpanjang Kabupaten Kepulauan Meranti - Muhammad Bakri; Nuryanti '; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was conducted to Employee Services Department PT. PLN (Persero) Branch Selatpanjang Meranti Islands Regency jl. Yos Sudarso.The purpose of this research to explain the variable employee commitmen and training in simultaneous and parcial to Employee productivity at service department PT.PLN (Persero) Cabang Selatpanjang Kabuapten Kepuluan Meranti. The population in this study were employees of PT Services Department. PLN (Persero) Branch Selatpanjang Meranti Islands Regency totaling 50 people. Sampel decision made by the census method as responden 50 samples, the method of analysis used is descriptive quantitative method by using SPSS version 18. From the results of simultaneous testing (F test) showed that the independent variables studied (Employee Commitment and Training) has a positive and significant effect on the variable (Employee Productivity) the magnitude of the effect that (R2) by these two variables together - equal to dependent variable 84.6% while the remaining 15.4%, influenced by variables - other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each - each variable studied bebas (Employee Commitment and Training) has a positive and significant impact on the dependent variable (Employee Productivity).Keywords: Commitment to Employees, Training and Employee Productivity